Impact of Mental Illnesses Treatment During the Period 1950-2020: Analysis of A Single Mental Institution, Buenos Aires, Argentina - Marín, Gustavo H. (2020)
Introduction: Mental health treatment has varied in the last century; however, the impact of these new therapeutical options is little-known. Objectives: To evaluate the impact of treatments for mental health diseases along the last decades. Methodology: retrospective, descriptive case-report study. Medical records of patients admitted to a Mental Health Institution in Buenos Aires, Argentina were evaluated over 7 decades. Variables analyzed were: age, sex, diagnosis, time of hospital stay, number of re-hospitalizations, drugs available per decade, cost of drug, cost of hospitalizations. Results: Hospitalization stay was 6.33 months, with 3.18 readmissions per patient (in the 21st century it was detected a reduction in the length of hospitalization (4.66 months) and an increase in the number of hospitalizations (4.3 hospitalizations/patient). The numer of drugs prescribed was 5.14 per patient (1.6 in the 1950s and 7.22 in the last decade). During 1950s, the most prescribed drugs were lithium and chlorpromazine, in the ’60s haloperidol; in the ‘70s benzodiazepines, haloperidol, and amitriptyline; in the ‘80s and ‘90s fluoxetine, sertraline, and BZD; from the 2000s paroxetine, risperidone, and pregabalin were added to the earlier drugs; and in the current decade new antipsychotics (olanzapine, ziprasidone, quetiapine or lurasidone), antiepileptics (lamotrigine) were included. Although diagnoses were maintained over time (schizophrenia, psychosis, bipolar disorder, dementia, depression) in the last decade, 27.7% of the hospitalized patients had dual pathology (addiction+other mental illness). Cost of drugs prescribed increased >9 times, while cost of hospitalization increased >4 times in the last decade compared to the second half of the 20th century. Conclusion: Although new drugs to treat severe mental disorders reduced side effects associate to treatment, its efficacy did not improve neither the duration of the hospital stay nor in the number of re-hospitalizations along the past 70 years; while cost of new drugs increased 9 times.